Parametric Analysis for 3D Modeling of Consolidation-Induced Solute Transport Using OpenFOAM - Bolin Wang; Dong-Sheng Jeng (Applied Sciences)
Most previous investigations for consolidation-induced solute transport models have been limited to one-dimensional studies in unsaturated porous media and lack systematic parameter sensitivity analysis. This study addresses these gaps by analyzing the effects of hydraulic conductivity (K), shear modulus (G), saturation (<semantics>Sr</semantics>), Poisson’s ratio (<semantics>ν</semantics>), partitioning coefficient (<semantics>Kd</semantics>), and anisotropy ratio (<semantics><mstyle scriptlevel="0" displaystyle="true">KxKz</mstyle></semantics> and <semantics><mstyle scriptlevel="0" displaystyle="true">KyKz</mstyle></semantics>) on pore water pressure, soil deformation, and solute transport. The findings reveal that higher <semantics>Kd</semantics> values significantly hinder solute migration through enhanced adsorption and reduced vertical transport to deeper layers, while increasing anisotropy ratios primarily enhance horizontal migration, with their effects diminishing beyond a threshold. Additionally, a higher K accelerates pressure dissipation and solute movement, while a lower G increases soil deformation and speeds up solute migration. Saturation has a minor effect on solute concentration, with slight increases under higher <semantics>Sr</semantics>. The Poisson ratio significantly impacts the transport of the solute, with smaller <semantics>ν</semantics> accelerating and larger <semantics>ν</semantics> slowing migration. These insights offer valuable theoretical support for optimizing models in unsaturated porous media.